Development of the typology of electoral groups of Ukraine on the basis of socio-psychological criteria - BEZRUKOVA, Kateryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The development of new approaches to the study of the electorate in the inter-election period is a rather urgent scientific challenge. The hypothesis was tested that socio-psychological features of voters are among the indicators that distinguish supporters of some political subjects from others and can be the basis for assigning voters to certain electoral groups. The purpose of this study was to determine the main electoral groups represented in Ukrainian society on the example of the city of Kyiv and the Kyiv region and to identify their differences based on the analysis of socio-psychological characteristics of voters. Methods. The research uses methods of online survey of respondents using a panel of psychological methods for researching personal traits, values, needs, political and ideological self-determination, political participation and activity, national identity, paternalism of voters, as well as methods of mathematical data processing. Results. Based on a retrospective analysis of the electoral choice in the 2019 presidential elections of Ukraine, an analysis of trust in President V. Zelensky and the respondents’ subjective assessment of the effectiveness of state authorities in domestic and foreign policy, it was possible to single out nine electoral groups in the electorate: convinced supporters of V. Zelensky, the newly arrived electorate of V. Zelensky, the negative supporters of V. Zelensky, the disillusioned electorate of V. Zelensky, the electorate of P. Poroshenko who has improved his attitude towards V. Zelensky, the electorate gravitating towards P. Poroshenko, convinced supporters of P. Poroshenko, newly arrived uncertain and scattered absentees. The features of each group are described according to socio-demographic and socio-psychological criteria. Conclusions. It is shown that electoral groups can be differentiated not only by socio-demographic features, but also by personal, value and other psychological characteristics. To confirm the effectiveness of the proposed model of differentiation of the electorate, it is considered appropriate to test the approach on a large representative sample through a nationwide survey.